An age-related difference in the size of the nasal glands of Brent Geese Branta bernicla - Summers, Ronald W; Smith, Malcolm M (Wildfowl, 1990)
We tested the hypothesis that the reason for early inland movement of Brent Geese during years in which the percentage of first-year birds was high, was that the nasal or 'salt' glands of the first-year birds were under-developed and thus less able to excrete the high salt levels ingested while grazing on intertidal vegetation. The data showed that the glands of first-year geese were heavier than those of the adults during November to February. Therefore, the hypothesis was not supported but, because of the timing of sampling, we do not discount the possibility that first-year geese have smaller glands when they arrive on wintering areas.